Perlindungan Hak Asasi Terdakwa Tindak Pidana Lalu Lintas dalam Sistem Peradilan Pidana di Indonesia - Sitorus, Boris Marisi; Hafrida; Siregar, Elizabeth (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
This study examines the protection of human rights afforded to defendants in traffic crime cases throughout the stages of the Indonesian criminal justice process. The analysis focuses on the fulfillment of fundamental rights as regulated in the Indonesian Criminal Procedure Code (KUHAP), the Traffic Law, Supreme Court Regulation No. 12 of 2016, and the principles of fair trial. This research employs a normative legal method with statutory, conceptual, and case approaches. The findings reveal that although the normative framework provides guarantees for defendants’ rights, implementation remains suboptimal, particularly regarding the right to legal assistance, the principle of equality of arms, procedural fairness, and proportionality in detention and evidentiary procedures. The study highlights the need for regulatory harmonization, stronger oversight mechanisms, and improved professionalism among law enforcement authorities to ensure effective protection of defendants’ rights in traffic crime cases.